ENGLISH AND INDONESIAN TYPES OF WARRANTS IN CLAIMS OF FACT, VALUE AND POLICY - Rohmani Nur Indah; Wenyk Ambarwati; Burhanudin Syaifulloh (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Warrant is a crucial element in argumentative essay which connects the claim and support in order to give proves that the supports are valid and credible. This study seeks the comparison between the warrant inn English and Indonesian argumentation. The rhetorical analysis in this study is to get deep understanding on the types of warrant that is used by the writers in the opinion section of www.theaustralian.com.au and www.seputar- indonesia.com in the claim of fact, of value, and of policy. The finding shows that on claims of fact, English writers show authoritative and substantive warrants while Indonesian writers prefer substantive and motivational warrants. In constructing the support for claims of value, almost similar result shown by both English and Indonesian writers that is the domination of motivational warrant. The writers attempt to strengthen the claims of policy show the use of substantive and motivational warrants by English writers. Meanwhile the Indonesian writers make use of substantive and authoritative warrants to convince the readers on the need to accept the proposed policy. Further studies are expected to dig more on the critical discourse analysis of warrants across different languages within different context, types of issue presented and different form of publication.